2020
DOI: 10.9734/aprj/2020/v6i430136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Fertilization and Amino Acids on Growth, Chemical Composition and Capsaicin Content of Hot Pepper (Capsicum annum L var. Minimum) Plant

Abstract: This investigation was conducted in a private farm, Samannoud district, El-Gharbia Governorate, Egypt, during two successive seasons of 2017 and 2018 to study the effect of organic fertilizers and foliar spray of amino acid on vegetative growth, fruit yield, chemical composition and capsaicin content of hot pepper (Capsicum annum L var. Minimum) plant. The experiment included 13 treatments obtained from cattle manure at rates of 60 and 30 N-units per fed. combined with amino acid at 0, 100 and 200 ppm as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…The results of capsaicinoid analysis showed that amino acid treatment had a positive effect on total capsaicinoids and individual capsaicinoids accumulation in pericarp and placenta of 'Chilli AS-Rot' and in placenta and seeds of 'Somborka' , which agrees with the results of Hammam, Eisa [43], who reported an increase in capsaicin in hot peppers after amino acid application. Interestingly, the amino acid treatment decreased the capsaicinoid content in 'Habanero Red Caribbean' placenta.…”
Section: Discussionsupporting
confidence: 89%
“…The results of capsaicinoid analysis showed that amino acid treatment had a positive effect on total capsaicinoids and individual capsaicinoids accumulation in pericarp and placenta of 'Chilli AS-Rot' and in placenta and seeds of 'Somborka' , which agrees with the results of Hammam, Eisa [43], who reported an increase in capsaicin in hot peppers after amino acid application. Interestingly, the amino acid treatment decreased the capsaicinoid content in 'Habanero Red Caribbean' placenta.…”
Section: Discussionsupporting
confidence: 89%